2022
DOI: 10.3389/fonc.2022.893124
|View full text |Cite
|
Sign up to set email alerts
|

Combination of 4-1BB and DAP10 promotes proliferation and persistence of NKG2D(bbz) CAR-T cells

Abstract: Chimeric antigen receptor (CAR)-T cell therapy has been shown to have considerable therapeutic effects in hematological malignancies, and NKG2D(z) CAR-T cell therapy has been verified to be safe based on clinical trials. However, due to the poor persistence of NKG2D(z) CAR-T cells, their therapeutic effect is not obvious. Here, we constructed NKG2D(bbz) CAR-T cells that can simultaneously activate 4-1BB and DAP10 costimulatory signaling. They were found to be cytotoxic to the target cells in vitro and in vivo.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 44 publications
(24 reference statements)
0
5
0
Order By: Relevance
“…In addition, the PI3K/AKT pathway is involved in T cell proliferation and differentiation, and it plays an important role in CAR-T cell exhaustion. At present, It has been confirmed that the PI3K inhibitor could modulate the differentiation of CAR-T cells and enhance the persistence of CAR-T cells in vivo (58)(59)(60). Intriguingly, a recent study found that the second generation tyrosine kinase inhibitor dasatinib could reverse the exhausted phenotype of CAR-T cells through increasing the expression of memory-associated genes, such as TCF7 and CCR7, and decreasing the expression of immune checkpoint molecule PD1 and exhaustion-related regulators, such as NR4A1, BATF3, ATF4, and FOS (61).…”
Section: Inhibiting Exhaustion-related Signalsmentioning
confidence: 88%
“…In addition, the PI3K/AKT pathway is involved in T cell proliferation and differentiation, and it plays an important role in CAR-T cell exhaustion. At present, It has been confirmed that the PI3K inhibitor could modulate the differentiation of CAR-T cells and enhance the persistence of CAR-T cells in vivo (58)(59)(60). Intriguingly, a recent study found that the second generation tyrosine kinase inhibitor dasatinib could reverse the exhausted phenotype of CAR-T cells through increasing the expression of memory-associated genes, such as TCF7 and CCR7, and decreasing the expression of immune checkpoint molecule PD1 and exhaustion-related regulators, such as NR4A1, BATF3, ATF4, and FOS (61).…”
Section: Inhibiting Exhaustion-related Signalsmentioning
confidence: 88%
“…However, third-generation CARs carry risks of off-target effects and excess cytokine production, with limited clinical data available. Consequently, fourth-generation CARs have been developed to address these concerns [43,44] Four Generation Fourth-generation CARs, derived from second-generation CARs, integrate domains regulating cytokine expression alongside costimulatory domains to bolster antitumor responses. These CARs, engineered to secrete IL-12, IL-18, or IL-21, enhance CAR-T cell cytotoxicity, proliferation, and memory T cell differentiation, thereby improving killing efficacy and sustaining antitumor effects in preclinical models [45][46][47]…”
Section: First Generationmentioning
confidence: 99%
“…Wei et al. reported that the simultaneous activation of the costimulatory signals 4-1BB and DAP10 on NKG2D CAR-T cells resulted in the poor differentiation of T cells in vitro and in vivo , upregulation of Bcl-2 expression, and an increased proportion of T SCM subsets ( 215 ). CAR-T cell adoptive transfer therapy results in significant antitumor activity, but this effect is observed only in a small group of patients.…”
Section: Targeting T-cell Exhaustion and T Scm To ...mentioning
confidence: 99%